Southern distribution limit of the European lobster, Homarus gammarus (Decapoda, Nephropidae) on the coast of northwest Africa with remarks on its habitat, and a new record from the Canary Islands - González Pérez, José Antonio (Crustaceana, 2022)
516 511 0,278 0,529 Q3 Q4 SCIE 11,0